Bernard Shaw and Totalitarianism Longing for Utopia - Yde, M.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
This book reveals the genuity of Shaw's totalitarianism by looking at his material - articles, speeches, letters, etc but is especially concerned with analyzing the utopian desire that runs through so many of Shaw's plays; looking at his political and eugenic utopianism as expressed in his drama and comparing this to his political totalitarianism.
Keywords: Theater; Literature; Theater—History.; Performing arts; British literature; Literature, Modern—20th century; Theatre and Performance Studies; Literature, general; Theatre History; Performing Arts; British and Irish Literature; Twentieth-Century Literature